IMPLEMENTASI KONSEP MULTI-NAS DENGAN MENGINTEGRASIKAN VPN SERVER DAN FREERADIUS SERVER DALAM MEMBANGUN SISTEM OTENTIKASI JARINGAN WIFI - Hanafi, Muh. Ibnu Habil; Raharjo, Suwanto; ., Suraya (Jurnal Jarkom, 2015)
ABSTRACTSome of WiFi networks is only provided the security with default security system, and some have not any security, and also the users management system for people who use the WiFi is not available. It can be occurred because a lack of oversight on development and maintenance the resources of WiFi network services. By analyzing the problems, it will be possible to get the best solution to generates a secure WiFi network services. Steps done in process of designing a network infrastructure on solution to generates a secure WiFi network services, Multi-NAS concept with FreeRADIUS server as authentication method and integration methods of VPN with FreeRADIUS server is can be used to support the purpose of designed network infrastructure. By implementing of those methods will be able to increase the security of WiFi network and user internet access. In the implementation process, data analysis is required to applying those methods in as an analysis infrastructure requirements by referring to the system that runs in infrastructure as basic knowledge of Linux, Mikrotik and Computer Networks. Thereby, implementation the method of authentication system on infrastructure will be provide a good security in the WiFi network and provide a secure users internet access of WiFi network. Â Keywords: WiFi, Server, FreeRADIUS, Network.